2021
DOI: 10.1002/pbc.29488
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of surgery for pulmonary metastases of hepatoblastoma with indocyanine green fluorescent imaging

Abstract: Background:The prognosis of metastatic hepatoblastoma remains poor; to improve it, pulmonary metastasis must be controlled. Indocyanine green (ICG) fluorescent imaging has been used recently for lung metastasectomy. The objective of our study was to clarify the usefulness of ICG imaging for lung metastasectomy of hepatoblastoma using detailed clinicopathological analysis.Procedure: Patients with hepatoblastoma who underwent resection of pulmonary metastases with ICG fluorescent imaging were studied using a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Those studies reported increased ICG uptake and impaired excretion of the fluorophore due to the tumor's biliary characteristics. 2,[22][23][24][25][26][27][28][29] However, the literature lacks information about nonhepatic tumor-related metastases and the feasibility and effectiveness of ICG application in those cases.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies reported increased ICG uptake and impaired excretion of the fluorophore due to the tumor's biliary characteristics. 2,[22][23][24][25][26][27][28][29] However, the literature lacks information about nonhepatic tumor-related metastases and the feasibility and effectiveness of ICG application in those cases.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary metastatic lesions are easily detected by ICG fluorescence due to the lack of ICG accumulation in normal lung tissue, which results in a clear contrast generated in pulmonary metastases of hepatocyte neoplasic cell such as HBs or hepatocarcinomas 3 . In addition, one of the limitations of ICG fluorescence imaging is its inability to probe deep tissue, as the fluorescence emitted by ICG can only penetrate 5–10 mm of tissue 2 . However, typical HB metastatic lesion location in peripheral pulmonary areas reduces the impact of this drawback 5 .…”
Section: Discussionmentioning
confidence: 99%
“… 3 In addition, one of the limitations of ICG fluorescence imaging is its inability to probe deep tissue, as the fluorescence emitted by ICG can only penetrate 5–10 mm of tissue. 2 However, typical HB metastatic lesion location in peripheral pulmonary areas reduces the impact of this drawback. 5 Moreover, intraoperative lung collapse by one‐lung ventilation may facilitate detection of the metastatic lesion if it is not near the surface of the lung once the lung has been collapsed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative labeling combined with minimally invasive resection of metastases has been developed during recent years to meet these challenges. Different techniques pursuing this approach have been described, some of them also in children [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 21 , 22 , 23 ]. These methods include labeling with Indocyanine Green (ICG) or other fluorescending agents, radionuclear labeling, or the use of hook wires.…”
Section: Discussionmentioning
confidence: 99%